INCREASING THE ECONOMIC VALUE OF BEEF CATTLE BUSINESS WASTE IN THE INTEGRATION SYSTEM WITH FOOD CROPS IN GORONTALO REGENCY, INDONESIA - Marwaty R.S.; Ihsan M.N.; Wisaptiningsih U.; Suyadi S. (Russian Journal of Agricultural and Socio-Economic Sciences, 2022)
Gorontalo Regency is part of the Gorontalo Province which is divided into 19 sub-districts that have the potential to develop beef cattle business. This research was conducted in 3 sub-districts and 6 villages in Gorontalo district from April to June 2018 using the survey method. Data were obtained from interviews, focus group discussions and filling out questionnaires from 100 respondents, while secondary data was obtained through documentation from reports from previous agencies and researchers. The data analysis used linear programming analysis. The linear programming model that was compiled to achieve the goal of maximizing the optimization model of farming and beef cattle business consisted of several alternative activities and resource constraints which were analyzed at the farmer level. The results showed that the potential availability of agricultural waste for food crops and cattle waste that owned by the farmers make it possible to implement integrated crop and livestock farming. Based on the allocation of land, labor, capital and feed availability, the ability of livestock to provide compost, the income obtained through the integration of rice-corn-cattle is 20.94 percent higher than without integration. Corn-cattle and rice-cattle are determined by the availability of the market for intermediate products and the level of crop production. Crop production that is low or below 50 percent of normal production results in lower income.